Karakteristik demografi dan tingkat pengetahuan sebagai faktor risiko masalah kesehatan gigi dan mulut anak - Septiana Karta, Maria; Gani Soulisa, Abdul; Hapsari Andayani, Lia (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
According to the Survei Kesehatan Indonesia 2023, the prevalence of dental caries in Indonesia reached 82.8%. The survey also revealed that the proportion of dental and oral health issues in the country was 56.9%. Dental caries and poor oral hygiene are common issues among primary school-aged children in Indonesia. The highest proportion of dental and oral health problems among school-aged children was observed in the 5-9 age group at 62.6%, followed by the 10-14 age group at 48.8%. Several factors were found to be associated with children's dental and oral health, such as demographic characteristics and levels of knowledge about dental and oral health. Age, gender, and parental occupation status are the demographic traits that have frequently been linked to population behaviour. Knowledge encompasses everything acquired through learning and sensory interactions, including taste, hearing, sight, and reasoning about specific subjects. In the context of dental and oral health, knowledge topics such as the development of cavities, primary causes of oral health issues, and effective treatments for maintaining oral hygiene. Various factors, such as education, occupation, age, gender, interests, experiences, and cultural influences, can impact an individual's level of understanding. Improving children's knowledge of oral health can significantly contribute to lowering the prevalence of dental caries.